قياس أثر عوامل الثقافة التنظيمية على جودة القرار الإداري: دراسة حالة مجموعة من مؤسسات بن حمادي ببرج بوعريريج - مهديد، فاطمة الزهراء (جامعة الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2017)
This study aimed to explore the impact of organizational culture on management quality decisions in a group of economics entreprises in Bordj Bou Arreridj, Achieving this study's objectives the researcher has conducted a survey on 4 Algerian Economic Enterprises from group Ben Hamadi by designing a questionnaire, where the study population consisted of all workers and administrators who are in various directorates of enterprises, and the choosing sample consisted of 66 individuals, and in the light of that, a collecting and analyzing data and testing hypotheses process has been carried out using the Statistical Package for Social Sciences (SPSS)., The study had reached to many important results , which are the organizational culture by its dimensions (Empowerment, cooperation, the quality of information, creative approach, and moral values) statistically have significant effects on the quality of management decisions in a group of Ben Hamadi enterprises active in the state of Bordj Bou Arreridj, The creative approach was more enplaning about the quality of decision, then it followed in order by the ranking quality of the information, Empowerment, and moral values.
هدفت هذه الدارسة إلى استكشاف أثر الثقافة التنظيمية على جودة القرارات الإدارية في عينة من المؤسسات الاقتصادية ببرج بوعريريج، ولتحقيق أهداف الدراسة أجرت الباحثة مسحا ميدانيا على 4 مؤسسات اقتصادية جزائرية من مجموعة بن حمادي، من خلال تصميم استمارة، حيث تكون مجتمع الدراسة من جميع الممال والإداريين المتواجدين في مختلف مديريات ودوائر المؤسسات، وقد تم اختيار العينة التي بلغ عددها 66 مفردة، وفي ضوء ذلك جرى جمع وتحليل البيانات واختبار الفرضيات باستخدام الحزمة الإحصائية للعلوم الاجتماعية SPSS، وتوصلت الدراسة إلى عدة نتائج أهمها وجود أثر ذو دلالة إحصائية للثقافة التنظيمية بأبعادها (التمكين، جودة المعلومات، التوجه الإبداعي، القيم الأخلاقية والتعاون) على جودة القرار الإداري عينة من المؤسسات التابعة لمجموعة بن حمادي الناشطة في ولاية برج بوعريريج، وكان التوجه الإبداعي أكثر تفسيرا لجودة القرار، ثم يليها على الترتيب جودة المعلومات، التمكين، والقيم الأخلاقية.
Keywords: الثقافه التنظيمية -- القرارات الإدارية -- المؤسسات الاقتصادية -- مؤسسات بن حمادى -- ولاية برج بوعريريج -- الجزائر